PERAN PEMERINTAH DALAM MENINGKATKAN AKSES DAN KUALITAS PENDIDIKAN UNTUK PEMENUHAN HAK WARGA NEGARA - Arif Fadilah; Masitoh; Ema Amelia Soraya (Cahaya Ilmu Bangsa Institute, 2024)
Education is a fundamental right ensured by both the constitution and international agreements as part of efforts to enhance the nation’s well-being. Nonetheless, problems related to access and the quality of education continue to be significant concerns that need to be tackled. This study explores the government's role in improving both access to and the quality of education to uphold the rights of citizens. The government acts as a facilitator, regulator, and provider of educational services through mandatory education policies, support for school operations, and inclusive education initiatives. This study also examines the challenges encountered, such as inequalities in access in rural regions, limited budgets, and the qualifications of teachers. Taking a comprehensive approach, this study suggests increasing the education budget, enhancing teacher training, and leveraging technology to ensure educational fairness.